Grain and size effect: a review on their influence in micro-manufacturing - Nur Ain Izzati, Zainudin (2013)
Size effects make most know-how of conventional machine is not suitable for the micromanufacturing process. Material behaviour greatly varies in micro-sheet forming process with different sheet thickness. In this research, a tensile test and grain size test was conducted to determine their mechanical properties of the materials and their influence in micro-manufacturing process. Firstly, the specimens were prepared according to the ASTM-E8 standard. After the hot mounting samples of the tested materials were prepared, grain size of the material is observed through SEM. According to tensile experiment, stressstrain curve was plotted while the patterns of grain for each specimen were discussed. Based on both result, the influence of size effects for thin sheet metal and bulk material in micro-manufacturing process is discussed and compared.